Konseling Kelompok Untuk Peningkatan Motivasi Belajar Dengan Pendekatan SFBC (Teknik Miracle Question) - Wijayanti, Tega (Universitas Nusantara PGRI Kediri, 2020)
Motivation to learn is something to stimulate students in carrying out learning activities to get a goal, namely achievement in learning. In learning activities, there will be active interactions that lead to the physical and mental development of students. So the authors conducted research on